Geometrical Knowledge in Early Sri Lanka - Jayawardana, Chandana (History of Science in South Asia)

(untitled) (University of Alberta Library, 2022)
This article addresses on history of mathematics (specially one of its specific branch, geometry) in Sri Lanka. Despite the large amount of research on the history of mathematics in India, China and the Middle East, that on Sri Lanka still remains limited. Sri Lanka had close relations with all these regions from ancient times and knowledge of mathematics should not be an alien subject there. This article tries to address the paucity of research on the history of mathematics in Sri Lanka while emphasizing the local character of that ancient knowledge.